IMPLEMENTATION OF THE RIGHTS OF SUSPECTS AS AN EMBODIMENT OF THE PRINCIPLE OF THE PRESUMPTION OF INNOCENCE IN THE EXAMINATION PROCESS AT THE INVESTIGATION LEVEL (CASE STUDY AT THE MEDAN POLRESTABES): IMPLEMENTASI HAK-HAK TERSANGKA SEBAGAI PERWUJUDAN ASAS PRADUGA TIDAK BERSALAH DALAM PROSES PEMERIKSAAN DI TINGKAT PENYIDIKAN (STUDI KASUS DI POLRESTABES MEDAN) - Lestari, Raya (LPPM UPMI, 2023)
The main problem in this research is the implementation of the suspect's rights in the examination process at the Investigation level. Therefore, this study aims to determine the implementation of the suspect's rights as the embodiment of the presumption of innocence at the Medan Polrestabes investigation level. to find out the obstacles of investigators in implementing the rights of suspects in the examination process at the Medan Polrestabes Investigation level. Data collection is done by means of observation, interviews. Based on the results of the research carried out, in the implementation of the suspect's rights in the examination process, regardless of whether the suspect is guilty or not, the right to be investigated immediately and the right to be free to provide information or in the sense that the suspect is examined during the examination, there is no pressure or physical violence during the examination. However, there is one right that is not in accordance with the rights of the suspect as regulated in the Criminal Procedure Code in which the suspect does not receive legal assistance. and the actions of law enforcement officers, in this case investigators in conducting examinations, are arrogant, they assume that they are the holders of the fate of the suspect, ignorance or lack of understanding is explained about the rights that can be obtained by the suspect and suspects who do not understand the importance of assistance. n the law, dishonesty and transparency of the suspect in carrying out the integration process (examination), and uncooperative suspects are usually passive and mostly silent.